Endothelial Dysfunction Is Associated with Mortality and Severity of Coagulopathy in Patients with Sepsis and Disseminated Intravascular Coagulation. (27th May 2019) - Walborn, Amanda; Rondina, Matthew; Mosier, Michael; Fareed, Jawed; Hoppensteadt, Debra
The role of the endothelium in sepsis-associated disseminated intravascular coagulation (DIC) is multifaceted and may contribute substantially to disease severity and outcome. The purpose of this study was to quantify measures of endothelial function, including markers of activation (endocan, Angiopoietin-2 [Ang-2], and von Willebrand Factor), endogenous anticoagulants (tissue factor pathway inhibitor and protein C), and damage-associated factors (High Mobility Group Box 1 [HMGB-1]) in the plasma of patients with sepsis and DIC, and to determine the relationship of these factors with severity of illness and outcome. Plasma samples were collected from 103 adult patients with sepsis within 48 hours of intensive care unit admission. Biomarker levels were measured using commercially available, standardized methods. Disseminated intravascular coagulation was diagnosed according to the International Society of Thrombosis and Hemostasis scoring algorithm. Twenty-eight-day mortality was used as the primary end point. In this study, endothelial damage and dysfunction were associated with the severity of coagulopathy and mortality in DIC patients. Loss of the endogenous anticoagulant protein C and elevation in the vascular regulator Ang-2 were associated with the development of overt DIC. In addition to Ang-2 and protein C, endocan, a biomarker of endothelial activation, and HMGB-1, a mediator of endothelial damage and activation, were significantly associated with mortality. This underscores the contribution of the endothelium to the pathogenesis of sepsis-associated DIC.